Firm-level employment growth in South Africa: The role of innovation and exports - Karmen Naidoo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper investigates the effect of innovation on employment growth at the firm level in South Africa. Innovation is typically associated with better export performance at the firm level due to productivity enhancements and new products. However, the link between innovation and employment is more ambiguous. R&D targeted towards product innovation has been typically associated with employment growth. Process innovations may have a positive effect, but also have the potential to reduce the demand for labour. This paper aims to isolate the impact of innovation on export performance to understand the direct and indirect channels through which innovation can influence employment growth. The analysis makes use of a novel administrative dataset of all registered firms in South Africa for the 2010-16 period. The study finds that, overall, direct innovation is positively associated with employment growth; however, the indirect innovation channel is negative and points to the idea that the productivity enhancements necessary for South African exporters to compete internationally might promote labour-saving innovations.
Keywords: O3; F16; J23; L25; 330; employment; exports; firm growth; R&D